ErbB Receptor Tyrosine Kinase: A Molecular Switch Between Cardiac and Neuroectoderm Specification in Human Pluripotent Stem Cells. (27th June 2016) - Ramachandra, Chrishan J. A.; Mehta, Ashish; Lua, Chong Hui; Chitre, Anuja; Ja, K. P. Myu Mai; Shim, Winston
Abstract: Mechanisms determining intrinsic differentiation bias inherent to human pluripotent stem cells (hPSCs) toward cardiogenic fate remain elusive. We evaluated the interplay between ErbB4 and Epidemal growth factor receptor (EGFR or ErbB1) in determining cardiac differentiation in vitro as these receptor tyrosine kinases are key to heart and brain development in vivo. Our results demonstrate that during cardiac differentiation, cell fate biases exist in hPSCs due to cardiac/neuroectoderm divergence post cardiac mesoderm stage. Stage-specific up-regulation of EGFR in concert with persistent Wnt3a signaling post cardiac mesoderm favors commitment toward neural progenitor cells (NPCs). Inhibition of EGFR abrogates these effects with enhanced (>twofold) cardiac differentiation efficiencies by increasing proliferation of Nkx2-5 expressing cardiac progenitors while reducing proliferation of Sox2 expressing NPCs. Forced overexpression of ErbB4 rescued cardiac commitment by augmenting Wnt11 signaling. Convergence between EGFR/ErbB4 and canonical/noncanonical Wnt signaling determines cardiogenic fate in hPSCs.